2022
DOI: 10.1021/acs.est.2c04864
|View full text |Cite
|
Sign up to set email alerts
|

Paints: A Source of Volatile PFAS in Air─Potential Implications for Inhalation Exposure

Abstract: Paints are widely used in indoor settings yet there are no data for volatile per-and polyfluoroalkyl substances (PFAS) for paints or knowledge if paints are potentially important sources of human exposure to PFAS. Different commercial paints (n = 27) were collected from local hardware stores and analyzed for volatile PFAS by gas chromatography−mass spectrometry (GC−MS), nonvolatile PFAS by liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-qTOF), and total fluorine by 19 F nuclear magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…This particular wristband sample could have been contaminated with glue or food-coloring ingredients, based on the participants’ comments in the questionnaire. Previous studies have reported that paints containing coloring ingredients can be sources of diPAPs and FTOHs . However, further investigation is needed to confirm the potential sources.…”
Section: Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This particular wristband sample could have been contaminated with glue or food-coloring ingredients, based on the participants’ comments in the questionnaire. Previous studies have reported that paints containing coloring ingredients can be sources of diPAPs and FTOHs . However, further investigation is needed to confirm the potential sources.…”
Section: Results and Discussionmentioning
confidence: 97%
“…In addition, concentrations of 6:2 diPAP were much higher than those of 8:2 diPAP. However, studies on atmospheric diPAPs remain limited, while several studies on diPAPs in indoor dust also found higher levels of 6:2 diPAP compared to 8:2 diPAP. , While acknowledging the potential contribution of the built environment, such as indoor paints, to atmospheric diPAPs in both samplers, our observation of a 10-fold higher total mass of diPAPs in silicone wristbands compared to PAWS suggests a distinct source. Therefore, we hypothesize that they may have been captured through dermal contact, considering the direct skin contact nature of wristbands.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 11 PFAS are logical candidates for experimental verification, biomonitoring, or environmental (e.g., indoor air, clothing, dust) measurements. The estimation analysis demonstrated in this work is independent of the source of neutral PFAS; however, prior measurements of FTOHs released from consumer products, including textiles, upholstery, and paint, at room temperature and in a heated environment are documented. …”
Section: Discussionmentioning
confidence: 97%
“…The indoor environment can be an important contributor to population exposures to per- and polyfluoroalkyl substances (PFAS). , Exposures may occur via inhalation of airborne particles and gases; dermal exposure by direct contact with PFAS-containing materials or from the air; ingestion of food, water, and dust; and mouthing of materials . PFAS are manufactured chemicals, many of which are persistent in the environment and bioaccumulative. Currently, it is estimated that thousands of different PFAS exist, either for use in industry and product manufacture or as precursors or breakdown products. , PFAS are commonly used in consumer products and articles as water- and stain-resistant or nonstick coatings and as surfactants. , Examples of products treated with PFAS include furnishings, carpets, functional apparel, outdoor gear, cookware, food-contact materials, paints, and cleaning products. Exposure to several PFAS has been linked to a number of adverse health outcomes in humans and wildlife; , however, the toxic potential of the majority of PFAS has not been studied to date .…”
Section: Introductionmentioning
confidence: 99%